Acanthamoeba rhinosinusitis: A paediatric case report and a review of the literature. Issue 3 (September 2015) - Cammaroto, Giovanni; Astorga, Francisco Javier; Navarro, Alexandra; Olive, Teresa; Pumarola, Felix
Abstract: Few cases of Acanthamoeba rhinosinusitis have been reported in literature so far. We report on a 3 years child affected by acute early T-cell Leukaemia who, after a treatment-induced immunodeficiency, developed Acanthamoeba rhinosinusitis. The disease was successfully treated with a combination of surgical and medical treatment. A review of the literature on the diagnosis and management of this pathology is also presented.